Case Report: Fiberoptic bronchoscopy and thoracoscopic surgery as a treatment for pulmonary mucormycosis in pediatric acute lymphoblastic leukemia - Jia, Zhenlei; Qian, Yujie; Zhang, Lili; Li, Yun; Chen, Zhiguo; Zhao, Ling; Du, Juan; Tuo, Guangxin; Yue, Fang (Frontiers in Pediatrics, 2025)
BackgroundMucormycosis, a severe disease caused by fungal infections of the Mucorales order, is a frequent cause of mortality in patients with hematological malignancies. Pulmonary mucormycosis represents a common form of this condition in pediatric patients with hematological malignancies and is associated with a high mortality rate. Liposomal amphotericin B (L-AmB) remains the primary therapeutic agent for pulmonary mucormycosis, however, its efficacy is often limited. We report a case of treating pulmonary mucormycosis in a pediatric patient with acute lymphoblastic leukemia (ALL) using fiberoptic bronchoscopy (FB) combined with thoracoscopic surgery, in conjunction with antifungal therapy including L-AmB.Case report and managementA 3-year-old male patient with a 1-year history of ALL. After the 11th chemotherapy session, the patient developed symptoms including fever, cough, and sputum production. Comprehensive diagnostic evaluations confirmed the presence of pulmonary mucormycosis in the right lung. On the basis of adequate administration of multiple antifungal agents, we conducted two fiberoptic bronchoscopy-guided bronchoalveolar lavage procedures for the child, successfully confining the lesion to the right upper lobe. However, the child continued to experience intermittent hemoptysis. Subsequently, we performed a thoracoscopic right upper lobectomy for the child. The child was discharged smoothly 9 days after the operation, and the postoperative pathology also indicated a fungal infection. One month postoperatively, a follow-up chest CT scan revealed no significant infection in either lung. Chemotherapy for ALL was continued. The child was followed up for three years after completion of treatment and remained in good health with no notable symptoms.ConclusionThe treatment of childhood ALL complicated with pulmonary mucormycosis is particularly challenging and associated with a high mortality rate. For children with severe infections, combining antifungal therapy, such as L-AmB, with bronchoscopy and thoracoscopic surgery has been shown to be both feasible and effective.